Onzekere veiligheid Verantwoordelijkheden rond fysieke veiligheid - Wetenschappelijke Raad voor het Regeringsbele (WRR Rapporten, 2008)
New technologies, climate change, infectious diseases and major crises like the BSE-affair make us realize that our knowledge of risks threatening our society is very limited. The shaping of the responsibilities of our physical safety has to be rethought. The WRR makes a strong case that government, companies and citizens alike should learn to cope pro-actively with uncertainties. This way they can be more aware of the vulnerability of nature, society and the people in it. The council gives suggestions how the government can stimulate this process.